2016
DOI: 10.1002/jmv.24645
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papillomavirus (HPV) 16, HPV18, and other HR‐HPV viral load and the histological classification of cervical lesions: Results from a large‐scale cross‐sectional study

Abstract: The relationship between HPV viral load and histological grades in the development of cervical cancer is in argument. It is helpful to better understand the association by quantitatively detecting viral load of HPV16, 18, and a pool of 12 other high-risk HPV type (OT) independently on the samples of precancer and cancer. A cross-sectional study was performed in five medical centers of China. Histological diagnosis made by local pathologists was adjudicated via a pathology expert panel. A fully automated real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 35 publications
5
36
1
2
Order By: Relevance
“…First, integration of HPV16 and HPV18 into the cellular genome may show differences (34). Second, differences are also found in the trends seen for presumptive viral loads from a normal cervix to SCC (35,36). Although evidence above has confirmed that HPV16 acts in malignant transformation differently from HPV18, our data show that the combined positivity rates of HPV16-E6 and HPV18-E6 in HPV16/18 coinfection were similar to their single infections counterparts, suggesting HPV16 and HPV18 might cause cervical lesion independently.…”
Section: Discussionmentioning
confidence: 99%
“…First, integration of HPV16 and HPV18 into the cellular genome may show differences (34). Second, differences are also found in the trends seen for presumptive viral loads from a normal cervix to SCC (35,36). Although evidence above has confirmed that HPV16 acts in malignant transformation differently from HPV18, our data show that the combined positivity rates of HPV16-E6 and HPV18-E6 in HPV16/18 coinfection were similar to their single infections counterparts, suggesting HPV16 and HPV18 might cause cervical lesion independently.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these assays were sufficiently sensitive to detect very low viral copy numbers (0.001 copies/μL) as well as able to detect values as high as 67 million copies/μL. Several previous studies have argued that a linear relationship between the severity of disease and viral load is associated with specific HPV types [15,16,17,18]. One study reported a significant relationship when the HPV types were 16, 31, 33, 52, and 58, while the association was not significant with HPV types 18, 45, 56, and 59 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Since the integration of the HPV DNA into the host cells is necessary for malignant transformation by the E6 and E7 proteins, the HBV DNA load has been suggested to be used as a marker of the risk of dysplasia and CC [17,23]. In addition, the quanti cation of the DNA load could have a direct relationship with the risk of cervical lesions [24][25][26]. Many HPV infections will not lead to cervical lesions since a persistent infection is necessary for malignant transformation, and many infections are self-resolving [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this association is still controversial [21,30]. Lorincz et al [21] reported that there was no association between the viral load of 13 HR-HPVs and the risk of CIN III and CC, while Wu et al [24] showed that the HPV-18 viral load was low in precancerous lesions but high in CC. On the other hand, the present study supports the hypothesis that high HR-HPV viral loads are associated with more advanced cervical lesions.…”
Section: Discussionmentioning
confidence: 99%